EFFECT OF POLYMERS ON THE PHYSICOCHEMICAL AND DRUG RELEASE PROPERTIES OF TRANSDERMAL PATCHES OF ATENOLOL - Kumar, Manish; Trivedi, Vishal; Shukla, Ajay Kumar; Dev, Suresh Kumar (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of this research work was to develop a transdermal drug delivery system containing atenolol with different ratios of hydrophilic and hydrophobic polymeric combinations, using solvent evaporation technique and to examine the effect of hydrophilicity and hydrophobicity of polymers on the physicochemical and drug release properties of transdermal patches. Methods: Solvent casting method has been used to formulate transdermal patches. Hydroxypropyl methylcellulose (HPMC), Polyvinylpyrrolidone (PVP), Ethylcellulose (EC) in different combination ratios were used as the polymer. Propylene glycol was used as a plasticizer. Permeation enhancers such as span 80 were used to enhance permeation through the skin. In vitro diffusion study was carried out by franz diffusion cell using egg membrane as a semi-permeable membrane for diffusion. Results: Result showed that the thickness of the all batch of patches varied from 0.32 to 0.39 mm with uniformity of thickness in each formulation. Formulations F1 to F3 had high moisture content varied from 2.07Â±0.09 to 2.56Â±0.15 and high moisture uptake value varied from 3.21Â±0.35 to 4.09Â±0.38, due to a higher concentration of hydrophilic polymers. Drug content of all batches was ranged between 85.92Â±1.32 to 95.71Â±1.42. Folding endurance values off all batches were more than 75. Formulation batches F1 to F3 showed higher cumulative drug release varied from 61.34% to 68.11% as compared to formulation batches F4 to F6. Conclusion: Higher proportion of hydrophilic polymer in the formulation of transdermal patches, gives higher percentage drug release from prepared patches. The finding of the study indicates that hydrophilicity and hydrophobicity of polymer effects the physicochemical and drug release properties of transdermal patches and an optimum proportion of hydrophilic and hydrophobic polymer is required for the preparation of effective transdermal patches.Â